2020
DOI: 10.1111/pcn.12980
|View full text |Cite
|
Sign up to set email alerts
|

[11C]raclopride positron emission tomography study of dopamine‐D2/3 receptor binding in patients with severe major depressive episodes before and after electroconvulsive therapy and compared to control subjects

Abstract: Aim The aim of the study was to test: (i) if D2/D3 binding in three functional subsections of striatum is different in patients with severe major depressive episodes than in controls; and (ii) if this difference is normalized after electroconvulsive therapy (ECT). Methods Nine inpatients were examined with positron emission tomography (PET) and the radioligand [11C]raclopride before and after an average of 8.4 ECT sessions. Treatment response was assessed using the Montgomery–Åsberg Depression Rating Scale. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
4
1
Order By: Relevance
“…Similarly, a different PET study using [ 11 C]raclopride (a selective dopamine D2/D3 antagonist tracer) found patients experiencing major depressive episodes had lower dopamine D2/D3 binding in the striatum compared to those who did not have depression. However, in this study, ECT did not result in a significant improvement in D2/D3 binding in patients with depression ( 84 ).…”
Section: The Utility Of Pet In the Treatment Of Depressioncontrasting
confidence: 75%
“…Similarly, a different PET study using [ 11 C]raclopride (a selective dopamine D2/D3 antagonist tracer) found patients experiencing major depressive episodes had lower dopamine D2/D3 binding in the striatum compared to those who did not have depression. However, in this study, ECT did not result in a significant improvement in D2/D3 binding in patients with depression ( 84 ).…”
Section: The Utility Of Pet In the Treatment Of Depressioncontrasting
confidence: 75%
“…VST is a core structure in the reward system and dopamine a major mediator of reward related behavior. Impaired reward reversal learning has indeed been demonstrated in MDD patients, along with reduced striatal activity during unexpected rewards and dopamine dysregulation 46,47 . Ketamine increases dopamine levels in the VST in rodents, even though ketamine-induced dopamine release appears less pronounced in humans 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the patient’s clinical response, it has been proven that the dopamine nervous system is part of the mechanism of ECT. Tiger et al [ 34 ] used PET and [ 11 C]raclopride to examine patients with severe MDD before and after ECT, and healthy controls. Compared with the control group, the [ 11 C]raclopride binding rate in all three parts of the striatum decreased significantly in the patients.…”
Section: Brain Functional Imaging Study For Depression With Ectmentioning
confidence: 99%